Cerebrovascular illness in the province of Cienfuegos. Tendency lines. A six years study - Rubén Bembibre Taboada; Pedro Orduñez García; Bárbaro Jova Roque; Idaylí Pérez Rodríguez; Dianarelys Villafuerte Delgado; Juan E. Domínguez Suárez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Background: The cerebrovascular diseases constitute the third cause of death and first of handicap in Cuba. They are inside the tasks prioritized by the World Health Organization and they receive special interest in Cienfuegos province, that is one of the populations of more longevity of the country and shows high rates of mortality. Objective: To define the tendency lines, according to the type of cerebrovascular diseases in Cienfuegos province, over the last six years. Methods: There was realized a retrospective, and descriptive study, of a series of cases. The mortality was analyzed for the different types of cerebrovascular diseases. The data were obtained, of the monthly and annual reports of the Commission of cerebrovascular diseases. Results: A half rate of morbidity of 108, 89, was verified by 100 000 habitants; the mortality due to infarct and subarachnoid hemorrhages diminishes. It was not the same in presence of intracerebral hemorrhage, in which was observed an increment. Increased the number of alive patients after the discharge from the hospital, which due to infarct and other cerebrovascular diseases, were handicapped and for their condition generated a load to the society. Conclusions: The intracerebral hemorrhage constitutes the main problem for the mortality and the infarct for the morbidity.